Multilayered Tablet Technology, Manufacturing Process, Evaluation and its Application Areas - KERİMOĞLU, OYA; UĞURLU, TİMUÇİN (MARMARA UNIV, FAC MEDICINE, 2016)
According to new developed technologies, drug industry is also trying to refresh and improve itself. With the conception of rational pharmacotherapy, new technologies becomes smarter than finding new active substances. Correspondingly as a new dosage system, multi-layer tablets that improved to serve this purpose, provides ease of use to patients, reduces the side effects and increases of effectiveness of active agent. Therefore multi-layer tablets are developed to improve both the quality of product and life. Conducted work studied for understanding the bi-layer tablet technique, evaluating the assesment parameters and to giving examples to used spaces.
Keywords: Bi-layer tablets; bi-layer tablet manufactoring; evoluation of tablets; tablet press; TENSILE STRENGTHS; EXTENDED-RELEASE; BILAYER TABLETS; DOSAGE FORMS; HYDROCHLORIDE; FORMULATION; POWDERS; PERFORMANCE; THERAPY; MATRIX